A atuação da pedagogia na educação infantil e a organização do fazer coletivo - Freitas, Idelice de Jesus Alves (2015)
The goal of this work is to reflect on the relevance of the function of the pedagogue as the pedagogic coordinator in Early Childhood Education. For this, the research of qualitative character intends, through bibliographic study and survey of documental data, to investigate the trajectory of the training and work of this professional in Brazilian education so as to perceive its importance in current times for the organization of the school work. One also used as a reference, the educational work carried out in a Municipal Center of Early Childhood Education situated in the East Zone of the city of Manaus-AM, with the intent of perceiving how the work of the pedagogue takes place in the structuring and implementation of the political pedagogical project of the institution. With the study it is observed in the talk of various authors, that upon building her professional identity the pedagogue is indispensable for the organization, systematization and coordination of the educational processes of the school. Through the data obtained one can perceive that the pedagogue confronted and confronts many adversities in her professional trajectory. However, upon organizing her work in favor of continuing education for teachers, of the collective organization of the school work and of the construction of a social environment of mutual respect, she consolidates herself as a pedagogic coordinator in Early Childhood Education and significantly contributes to the formation of thinking subjects.